PENGARUH KINERJA KEUANGAN, HUMAN CAPITAL, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Rahandhika Ivan Adyaksana; M. Sulkhanul Umam; Chily Meilia Singgangsari (Jurnal Aplikasi Akuntansi, 2023)
This research is used to examine the effect of financial performance, human capital, and environmental performance on firm value. This type of research is quantitative research using secondary data with data analysis techniques using multiple linear regression analysis obtained from the company's annual report. The research population is a non-cyclical consumer sector company that has been listed on the IDX from 2016-2020. Purposive sampling is a method in taking the sample of this study. The number of samples obtained is 17 companies with a research period of five years, so the total observations are 85 observations. The independent variables are financial performance, human capital, and environmental performance, while the dependent variable is firm value. The research was conducted using data analysis with SPSS 22 software. The results of this research have provided evidence that financial performance and human capital have a positive and significant effect on firm value. Meanwhile, environmental performance has a positive and insignificant effect on firm value.